SOME ASPECTS OF THE OBJECT AND SUBJECT OF THE CORPUS DELICTI PROVIDED FOR IN ARTICLE 273 OF THE CRIMINAL CODE OF THE REPUBLIC OF UZBEKISTAN - Gazibekov Khurshid Iskandarovich (International Journal of Business, Law and Political Science, 2024)
This article investigates the object and subject of the corpus delicti outlined in Article 273 of the Criminal Code of the Republic of Uzbekistan, focusing on the legal ramifications surrounding drug-related offenses. General Background: The increasing prevalence of narcotic drugs and psychotropic substances has prompted legal reforms to address drug-related crimes effectively. Specific Background: Article 273 identifies various categories of illicit substances, including narcotic drugs, psychotropic substances, and their analogues, along with precursors used in their production. Knowledge Gap: However, the absence of a comprehensive list of drug analogues creates ambiguity regarding legal responsibility, complicating the prosecution of offenders under this article. Aims: This study aims to elucidate the generic, specific, and immediate objects of the crime, while critically assessing the implications of undefined analogues in the context of legal accountability. Results: The findings reveal that the lack of clarity regarding the classification of drug analogues may hinder the enforcement of Article 273, resulting in potential challenges in ensuring justice. Novelty: This research contributes to the existing body of knowledge by highlighting the necessity for a precise legal framework that encompasses all forms of narcotic substances and their analogues. Implications: The insights derived from this analysis underscore the urgent need for legislative reform to establish clear definitions and lists of drug analogues, thereby enhancing the effectiveness of the legal system in combating drug-related crimes and protecting public health.